I-checkin@PKB: The acceptance among Politeknik Kota Bharu staff - Mohd Zaidi Che Mod; Kamilah Zainuddin; Noor Asmaa’ Hussein; Asmaa AlSaqqaf; Deepak Pantha (Penerbit UPSI, 2024)
I-Checkin@PKB has been utilized at Politeknik Kota Bharu (PKB) for nearly six months, replacing the thumbprint attendance monitoring system. With I-Checkin@PKB, users can eliminate the need to wait in line at the centralized terminal for attendance registration, making it more efficient and hygienic. This system helps avoid potential germ transmission through contact with the same terminal, particularly amidst the challenges posed by Covid-19 and viral fever outbreaks. While the management of PKB has received verbal feedback from users, the actual level of user acceptance regarding I-Checkin@PKB remains unknown. Therefore, this study aims to investigate the acceptance level among I-Checkin@PKB users, focusing on perceived ease of use, perceived usefulness, attention to use, and behavioral intention. The study involved 100 respondents selected through random sampling. Utilizing 12 items with a Cronbach Alpha reliability coefficient of α=0.97, representing the constructs, the results indicated a high level of acceptance among users regarding I-Checkin@PKB, including its ease of use, usefulness, attention, and behavioral intention. Furthermore, the positive perceptions among I-Checkin@PKB users are likely to garner continuous support due to its ability to reduce the risk of human error associated with manual methods, such as paper-based attendance sheets. It is crucial to emphasize that while I-Checkin@PKB systems offer numerous benefits, their successful implementation necessitates clear communication, employee training, and consideration of privacy and security concerns to ensure a positive experience for both employees and the organization.